Reconsidering the inclusion of Ladapo's work in the meta-analysis: Validity concerns and implications - Borja Somovilla Del Saz (Taylor & Francis Group, 2024)
ABSTRACTThis is a response to Marchand & Masoud's response letter regarding my criticism "Response to Dr. Somovilla del Saz's letter to the editor regarding "Risk of all-cause and cardiac-related mortality after vaccination against COVID-19: A meta-analysis of self-controlled case series studies."" The response is a defense of the initial criticism to the paper regarding the validity of the inclusion of Ladapo´s paper.